2019
DOI: 10.1021/acsami.9b17631
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition and Interdigitation of Alkyl Side Chains in the Conjugated Polymer Poly(3-hexylthiophene) and Their Effects on the Device Performance of the Associated Organic Field-Effect Transistor

Abstract: Direct grazing-angle X-ray scattering evidence of the order–disorder transition and interdigitation of side chains in a conjugated polymer poly­(3-hexylthiophene) (P3HT) is presented. The free methyl ends of the side chains exhibit closest packing, as in n-alkane crystallization, and cause a structural mismatch due to the difference between their packing density and the areal density of the attached ends. This mismatch is resolved by increases in the tilt angle of the side chains and local interdigitation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…Unlike PBOBDTBTD, the PBOBDTTh has a less rigid thiophene structure than the former's benzothiadiazole ring. For this reason, PBOBDTTh polymer is expected to be less rigid, as already verified by other authors who reported that rigidity of conjugated backbones decreases when the polymer has a higher degree of alkyl substitution in the main chain [25,26], additionally, it also has been observed that the introduction of more flexible bonds in the polymer backbone substantially increases chain flexibility [27]. Figure 4 displays the evolution as a function of annealing time at 140 8C of the peak detected at low q values for PBOBDTTh, associated with the plane perpendicular to the conjugated plane, i.e., associated with the side alkyl chain.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Unlike PBOBDTBTD, the PBOBDTTh has a less rigid thiophene structure than the former's benzothiadiazole ring. For this reason, PBOBDTTh polymer is expected to be less rigid, as already verified by other authors who reported that rigidity of conjugated backbones decreases when the polymer has a higher degree of alkyl substitution in the main chain [25,26], additionally, it also has been observed that the introduction of more flexible bonds in the polymer backbone substantially increases chain flexibility [27]. Figure 4 displays the evolution as a function of annealing time at 140 8C of the peak detected at low q values for PBOBDTTh, associated with the plane perpendicular to the conjugated plane, i.e., associated with the side alkyl chain.…”
Section: Resultssupporting
confidence: 60%
“…This effect is stronger in the case of alkyl branches as presented for PBOBDTBTD and PBOBDTTh. Figure 8 illustrates in a schematic representation with a benzodithiophene conjugated polymer for the presently studied polymer films how the average interplanar distances may be higher with the advance of annealing, explained by the evidence found by [26] on the structural mismatch between chain ends and the chain start of the adjacent backbone in the crystallite, which could be evidence of the absence of alkyl chain interdigitation in the ordered regions. Interestingly, the increase of interplanar distance during crystallization is less pronounced for PBOBDTTh than for the others.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, high sidechain attachment density prevents sidechain interdigitation and long-range intermolecular organization. For example, the sidechain density in P3HT is too large to permit interdigitation when the backbone is well packed 119 and mostly results in two-dimensionally ordered, smectic-like structure without registry between layers. In contrast, the side-chain attachment densities of PBTTT and PQT are sufficiently low to permit the interdigitation of side chains, which preserves the packing structure by interlocking adjacent layers and thus promote three-dimensional order.…”
Section: Toward Polymer Crystals With G < 5% and Long Coherence Lengthmentioning
confidence: 99%